2006
DOI: 10.1103/physrevlett.97.036601
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Thermopower and Planar Nernst Effect inGa1xMnxAsFerromagnetic Semiconductors

Abstract: We present the first experimental study of the thermopower in Mn-doped GaAs ferromagnetic semiconductors. Large magnetothermopower effects in both longitudinal and transverse directions have been observed below the ferromagnetic transition temperature. Unlike magnetoresistance, neither the transverse thermopower (planar Nernst effect) nor the longitudinal thermopower explicitly depend on the strength of the in-plane magnetic field, but rather are intimately related to each other through the magnetization. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 17 publications
6
57
1
Order By: Relevance
“…Therefore, other metals with smaller spin-orbit coupling than Pt, not so close to a magnetic instability, should probably be used instead to detect the intrinsic SSE [27]. In any case, our results put an upper limit to the possible observation [28], and Pt/YIG bilayers [24], and can be understood in terms of the Mott relationship between the anomalous Nernst and Hall coefficients [28,29,30,31]. This means that the ANE must be determined by the energy dependence of its electrical charge counterpart: Where  xy =  M z  xx n is the anomalous Hall resistivity [32,33].…”
mentioning
confidence: 83%
“…Therefore, other metals with smaller spin-orbit coupling than Pt, not so close to a magnetic instability, should probably be used instead to detect the intrinsic SSE [27]. In any case, our results put an upper limit to the possible observation [28], and Pt/YIG bilayers [24], and can be understood in terms of the Mott relationship between the anomalous Nernst and Hall coefficients [28,29,30,31]. This means that the ANE must be determined by the energy dependence of its electrical charge counterpart: Where  xy =  M z  xx n is the anomalous Hall resistivity [32,33].…”
mentioning
confidence: 83%
“…In GaMnAs the planar [35] and anomalous [36] Nernst effects have been observed, with intriguing temperature dependences. Slachter et al [37] identified the anomalous Nernst effect and anisotropic magnetoheating in multiterminal permalloy|copper spin valves.…”
Section: B Thermal Hall Effectsmentioning
confidence: 99%
“…However, it turned out that the TSSE [3][4][5][6][7][8][9][10][11][12][13][14][15][16], especially when using metallic ferromagnets [3-7, 13, 15, 16], is under strong discussion. Other magneto-thermoelectric effects, like the anomalous Nernst effect (ANE) [6,7,[15][16][17] and the anisotropic magneto-thermopower (AMTEP, also known as the planar Nernst effect (PNE)) [4,15,16,18,19] play an important role in the TSSE measurements and contribute to the detected signals. ANE and TSSE signals are antisymmetric with respect to the external magnetic field, have the shape of hysteresis loops and both follow the cos Θ 0 dependence, where Θ 0 is the angle between the magnetization vector M and the temperature gradient ∇T .…”
Section: Introductionmentioning
confidence: 99%